(Re) defining salesperson motivation: current status, main challenges, and research directions. Issue 1 (2nd January 2018) - Khusainova, Rushana; de Jong, Ad; Lee, Nick; Marshall, Greg W.; Rudd, John M.
Abstract : The construct of motivation is one of the central themes in selling and sales management research. Yet, to-date no review article exists that surveys the construct (both from an extrinsic and intrinsic motivation context), critically evaluates its current status, examines various key challenges apparent from the extant research, and suggests new research opportunities based on a thorough review of past work. The authors explore how motivation is defined, major theories underpinning motivation, how motivation has historically been measured, and key methodologies used over time. In addition, attention is given to principal drivers and outcomes of salesperson motivation. A summarizing appendix of key articles in salesperson motivation is provided.